Mammary analogue secretory carcinoma of the parotid gland—a rare tumour entity - Syeda Tehmina Junaid; Soima Ali Muhammad; Zeba Ahmed; Khubeb; Rajesh Kumar Vasandani; Jawad Ahmed (Journal of the Pakistan Medical Association, 2023)
Mammary analogue secretory carcinoma (MASC) is a salivary gland tumour with low-grade potential and specific FTV6 derangement having translocation of chromosomes t (12;15) (p13;q25). It shares a similar morphological as well as an immunohistochemical profile with secretory carcinoma (SC) of the breast making it a diagnostic enigma. In this report, we discuss the case of a 65-year-old male patient, who presented with a complaint of right-sided facial swelling. To rule out the differential, he underwent various diagnostic modalities, including magnetic resonance imaging, fine-needle aspiration and it’s the tumour’s microscopic and immunohistochemical properties were also reviewed. Parotidectomy along with concurrent chemo-radiotherapy was performed to eradicate the growing mass. Keywords: Mammary analogue secretory carcinoma, immunohistochemical, Parotidectomy.